Comparison of Ophthalmology Visits at Family Medical Center Hospital Before and During COVID-19 Pandemic - Michael Indra Lesmana; Kristian Goenawan; Maximillian Justin Irawan (Jurnal MedScientiae, 2022)
During this COVID-19 pandemic, many people are afraid of getting the disease or close relatives are afraid of getting it too, making people reluctant to leave the house. The government has also issued several strict regulations such as PSBB or PPKM which will certainly affect ophthalmology visits. Objective for knowing whether there was a decrease in the number of ophthalmology visits who came before the pandemic and during the pandemic. This study used descriptive analysis with a total of 9874 visits that met the inclusion and exclusion criteria. Data were collected using medical records. The average visit before the COVID-19 pandemic was 197.75 patients per month. During the COVID-19 pandemic it was 100.59, signifying a decrease of 49.13%. There was a decrease in the number of visits before and during the COVID-19 pandemic at the Bogor Family Medical Center Hospital, especially when the regulations were issued.